Orbital Atherectomy for Treating De Novo Severely Calcified Coronary Narrowing (1-Year Results from the Pivotal ORBIT II Trial) - Généreux, Philippe; Lee, Arthur C.; Kim, Christopher Y.; Lee, Michael; Shlofmitz, Richard; Moses, Jeffrey W.; Stone, Gregg W.; Chambers, Jeff W. (The American journal of cardiology, 2015)
Percutaneous coronary intervention of severely calcified lesions has historically been associated with major adverse cardiac event (MACE) rates as high as 30%. In the ORBIT II (Evaluate the Safety and Efficacy of OAS in Treating Severely Calcified Coronary Lesions) trial, treatment of de novo severely calcified lesions with the Diamondback 360° Coronary Orbital Atherectomy System (OAS) resulted in low rates of procedural and 30-day adverse ischemic events. The long-term results from this trial have not been reported. We sought to determine the 1-year outcomes after orbital atherectomy of severely calcified coronary lesions. ORBIT II was a single-arm trial enrolling 443 subjects at 49 US sites with severely calcified lesions usually excluded from randomized trials. OAS utilizes a centrifugal differential sanding mechanism of action for plaque modification prior to stent implantation. After OAS drug-eluting stents were implanted in 88.2% of the patients. The primary safety end point was 30-day MACE, the composite of cardiac death, myocardial infarction, or target vessel revascularization [TVR]. The present analysis reports the 1-year follow-up results from ORBIT II. One-year data were available in 433 of 443 patients (97.7%), with median follow-up time of 16.7 months. The 1-year MACE rate was 16.4%, including cardiac death (3.0%), myocardial infarction (9.7%), and target vessel revascularization (5.9%). The 1-year target lesion revascularization rate was 4.7%, and stent thrombosis occurred in 1 patient (0.2%). Independent predictors of 1-year MACE and target vessel revascularization were diameter stenosis at baseline and the use of bare-metal stents. In patients with severely calcified lesions who underwent percutaneous coronary intervention, the use of OAS was associated with low rates of 1-year adverse ischemic events compared with historical controls. This finding has important clinical implications for the selection of optimum treatment strategies for patients with severely calcified lesions.